SONG OF SURVIVAL: MELODIES OF IDENTITY, DISPLACEMENT, RESISTANCE, AND HOPE IN “WAVIN' FLAG” BY K'NAAN - Tan Michael Chandra (Faculty of Letters Universitas Balikpapan, 2024)
This research explores the themes of identity, displacement, resistance, and hope within K'naan's song